Cost Comparison Between Defocus Spectacle Lens and Compound Atropine in Myopia Treatment in the Portuguese Setting - Barros da Silva, P (2024)
INTRODUCTION: The rising prevalence of myopia poses a substantial global concern. Low concentration atropine and defocus spectacle lens (DSL) are the most widely used myopia prevention treatment in Portugal. Atropine drops must be compounded in pharmacies, because there is still no commercial low concentration atropine approved in Portugal. There are no studies with enough evidence to prefer one treatment over the other, so cost might be a decisive factor. Our purpose was to compare the costs between DSL and compound atropine for myopia progression prevention in Portugal. METHODS: We collected data on compound atropine from different pharmacies in Portugal, monofocal (MF) lenses prices from the four most common brands in Portugal and DSL price from brand representatives. Cost estimates were done per year of four consecutive years of myopia prevention treatment, considering different scenarios according to the need of spectacle lens exchange. We compared costs of low dose compound atropine plus MF lens versus DSL in the different scenarios. RESULTS: Atropine treatment proved more cost-effective than DSL treatment only when there was a requirement for lens exchange every 6 months or less (609.25€ for atropine versus 780.00€ for DSL per year of treatment). When myopia progression prevention is more effectiveand the need of lens exchange is equal or greater than 12 months, DSL treatment showed to be less expensive than mean values of atropine treatment plus MF lens (390.00€ for DSL vs 464.59€ for atropine, per year of treatment). CONCLUSION: DSL take a cost advantage in prevention of myopia progression, in situations when there is a need of lens exchange within once a year or less frequently. However, atropine plus MF lenses might be a less expensive in cases whenever there is a need of lens exchange every 6 months or more frequently. It is essential to conduct further studies focusing on the costeffectiveness of different treatment options for preventing myopia progression